Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2393-12-97
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of maternal age, race/ethnicity and insurance on neonatal intensive care unit admission rates

Abstract: BackgroundMaternal race/ethnicity, age, and socioeconomic status (SES) are important factors determining birth outcome. Previous studies have demonstrated that, teenagers, and mothers with advanced maternal age (AMA), and Black/Non-Hispanic race/ethnicity can independently increase the risk for a poor pregnancy outcome. Similarly, public insurance has been associated with suboptimal health outcomes. The interaction and impact on the risk of a pregnancy resulting in a NICU admission has not been studied. Our ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 12 publications
(12 reference statements)
2
25
0
Order By: Relevance
“…Both advancing age as well as pregnancies at younger age have been reported to be associated with risk of NICU admission. [6][7][8] In India, prevalence of teenage pregnancies has been reported to be varying from 8.7% to 24% from various set ups. [9][10][11] On the other hand prevalence of late pregnancy (in fourth decade or above) is relatively lowers (6.5%) in India.…”
Section: Discussionmentioning
confidence: 99%
“…Both advancing age as well as pregnancies at younger age have been reported to be associated with risk of NICU admission. [6][7][8] In India, prevalence of teenage pregnancies has been reported to be varying from 8.7% to 24% from various set ups. [9][10][11] On the other hand prevalence of late pregnancy (in fourth decade or above) is relatively lowers (6.5%) in India.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on racial disparity in the United States show that African American infants have worse birth outcomes requiring higher rates of NICU admission. 18 Therefore, the reason for our study finding maybe multifactorial and perhaps related to poor birth outcomes and comorbid medical illness rather than the actual decision to perform biopsy.…”
Section: Discussionmentioning
confidence: 87%
“…The number of NICU admissions increased with maternal age, probably because of increased preterm birth and other complications. 12,13 The mean duration of stay in NICU was 10.67±6.29 days, and in 59% of the subjects (n=89) the duration of stay ranged from 5 to 12 days, 44 of them being preterm. Some studies have observed a good correlation between the gestational ages, birth weight and head circumference, and the duration of stay.…”
Section: Resultsmentioning
confidence: 99%